Develop an online system for 66kV sheath fault detection/location - Tan, Sylvia Pin Jie (Nanyang Technological University, 2021)
In an operation of power cables, it is important to keep track of sheath insulation as unhealthy cables usually leads to many problems. If there are insulation faults in the sheath, the cable's life will be shortened overtime due to overheating and water seeping into the cables. The disruptions to power will therefore affect the operations of many industrial and commercial-related businesses. Some of the problems are burnt-out light bulb, tripping breakers and dead outlets, etc. It is very important to detect any incipient insulation faults on the cables before they can cause any potential disruptions such as water seeping into the cables or overheating of cables, causing the cables to easily wear out. By conducting frequent preventive maintenance and checking on the cable systems, these unnecessary power interruptions can be avoided. There are many sheath faults locating techniques that are being used in the industry, such as Cable Sheath Resistance Test and Travelling Wave Test [1]. However, cables have to be de-energised during these tests due to safety reasons, resulting in the unavoidable disruption time. Cable Sheath Resistance Test will have to inject DC voltage into the cable sheath, and this will shorten the lifespan of the cables in a long run. Therefore, it is ideal to develop a technique that allows sheath check to occur without the need of de-energising the cables. In this project, the aim is to develop another alternative to do sheath check without the need of de-energising of the cables. By doing so, two methods have been suggested in the report. One of the methods is by using sheath currents, and the other is by using singularity of sheath impedance matrix. Both methods do not require de-energising of cables and therefore does not shorten the cables’ lifespan.